The impact of caregiver‐mediated JASPER on child restricted and repetitive behaviors and caregiver responses. Issue 5 (2nd December 2016) - Harrop, Clare; Gulsrud, Amanda; Shih, Wendy; Hovsepyan, Lilit; Kasari, Connie
Abstract : Restricted and repetitive behaviors (RRBs) are a core feature of autism spectrum disorder (ASD). Compared to the social‐communication impairments, we know considerably less about why children engage in RRBs and if and how to intervene with these behaviors. As a result, early intervention has typically focused on social‐communication. In this study, we were interested in understanding how child RRBs changed following an intervention targeting social‐communication behaviors and if caregiver training changed how they responded to their child's RRBs. Eighty‐six toddlers with ASD and their caregivers received one of two interventions: caregivers were either actively coached while playing with their child (JASPER) or attended information sessions about ASD. On three different occasions (when they entered the study, following 10 weeks of intervention and 6‐months after) caregivers were filmed playing with their child. From these recordings, we coded child RRBs and caregiver responses to these behaviors. Child RRBs remained relatively stable following intervention in both groups, but increased when the children returned at 6‐months. Caregivers who received one‐on‐one coaching (JASPER) responded to a greater number of their child's RRBs and their responses were rated as more successful. Our study showed that a short‐term social‐communication intervention delivered through caregivers had "spillover effects" on how they also responded to their child's RRBs. Interventions targeting social‐communication behaviors should also examine how these treatments affect child RRBs and how caregiver responses to these behaviors may change following training. Autism Res 2017, 10: 983–992 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.